Local climate governance: towards more interactive practices and settings? - Evers, Adalbert; Schmid, Verena (Voluntas, 2025)
While environmental challenges are high on the public agenda, they have raised many questions concerning the ability of society and politics to cope with them. In liberal democracies, they challenge the traditional interplay between the state, business sector, and the various forces of civil society. Relating to the concepts of a more interactive and collaborative governance agenda, this study focuses on the local level of climate governance in municipalities and urban politics. It is based on material, documents, and interviews with representatives of public administration and civil society from seven major towns in Baden-Württemberg, Germany. Our findings show progress in local governance, driven by municipal climate action plans, the recognition of climate action as a cross-cutting issue, and the influence of national and federal policies and programmes. The study identifies four main forms of revitalising and institutionalising intermediation across sectors: (1) public participation through various formats meant to give citizens a voice; (2) stakeholder involvement for co-designing measures and plans by partners and opponents most affected; (3) strategies of influencing public opinion and the prevailing discourse on climate politics; and (4) forms of co-production in policy implementation. While the impact of these forms of conflict management, bridge-building, or even cooperation may vary, they altogether define the nature of local interactive governance and its capacities for promoting sustainable development and democracy.
Online veröffentlicht: 25 November 2024
Gesehen am 23.06.2025